Proteome-defined changes in cellular pathways for decidua and trophoblast tissues associated with location and viability of early-stage pregnancy - Lynn A. Beer; Suneeta Senapati; Mary D. Sammel; Kurt T. Barnhart; Courtney A. Schreiber; David W. Speicher (BMC, 2022)
Abstract Background In early pregnancy, differentiating between a normal intrauterine pregnancy (IUP) and abnormal gestations including early pregnancy loss (EPL) or ectopic pregnancy (EP) is a major clinical challenge when ultrasound is not yet diagnostic. Clinical treatments for these outcomes are drastically different making early, accurate diagnosis imperative. Hence, a greater understanding of the biological mechanisms involved in these early pregnancy complications could lead to new molecular diagnostics. Methods Trophoblast and endometrial tissue was collected from consenting women having an IUP (n = 4), EPL (n = 4), or EP (n = 2). Samples were analyzed by LC-MS/MS followed by a label-free proteomics analysis in an exploratory study. For each tissue type, pairwise comparisons of different pregnancy outcomes (EPL vs. IUP and EP vs. IUP) were performed, and protein changes having a fold change ≥ 3 and a Student's t-test p-value ≤ 0.05 were defined as significant. Pathway and network classification tools were used to group significantly changing proteins based on their functional similarities. Results A total of 4792 and 4757 proteins were identified in decidua and trophoblast proteomes. For decidua, 125 protein levels (2.6% of the proteome) were significantly different between EP and IUP, whereas EPL and IUP decidua were more similar with only 68 (1.4%) differences. For trophoblasts, there were 66 (1.4%) differences between EPL and IUP. However, the largest group of 344 differences (7.2%) was observed between EP and IUP trophoblasts. In both tissues, proteins associated with ECM remodeling, cell adhesion and metabolic pathways showed decreases in EP specimens compared with IUP and EPL. In trophoblasts, EP showed elevation of inflammatory and immune response pathways. Conclusions Overall, differences between an EP and IUP are greater than the changes observed when comparing ongoing IUP and nonviable intrauterine pregnancies (EPL) in both decidua and trophoblast proteomes. Furthermore, differences between EP and IUP were much higher in the trophoblast than in the decidua. This observation is true for the total number of protein changes as well as the extent of changes in upstream regulators and related pathways. This suggests that biomarkers and mechanisms of trophoblast function may be the best predictors of early pregnancy location and viability.